PRESENTATION OF PERTINENT DATA IN FINANCIAL STATEMENTS. - King, Earle C. (The Accounting Review, 1948)
Abstract From the outset the U.S. Securities and Exchange Commission has been sympathetic to this point of view and has sought the advice of leading accounting authorities in teaching, public practice, and among executives of corporations investment bankers, and financial analysts in the preparation of rules, regulations, and forms necessary in the administration of the acts which authorize the Commission to prescribe the forms, items, and details of financial statements to be filed generally, uniform systems of accounts, principles to be followed by registered investment companies in maintaining their accounting records and in preparing financial statements. On individual problems, however, where experience has disclosed serious discrepancies in practice as between companies and accountants and one has felt that uniformity in procedure would benefit investors by rule or regulation of the Commission or in an opinion of the chief accountant. It is imperative, therefore, that the Commission make certain that the financial statements contained in registration statements be completely unequivocal and are not used as a proving ground for innovational presentations.